Konsepsi Filsafat Idealisme Dalam Penerapan Pembelajaran Di Sekolah Dasar - Fitria Sari; Elsa Chaeratunnisa; Sholeh Hidayat (Literasi: Jurnal Ilmu Pendidikan, 2024)
This research discusses the conception of the philosophy of idealism and its implementation in the context of learning in elementary schools. The philosophy of idealism includes the view that world reality is formed by ideas and thoughts, placing emphasis on spiritual values and abstract concepts. The main aim of this research is to understand how the philosophical conception of idealism is reflected in learning strategies and methods in the elementary school environment. The research method used is literature study and content analysis to explore the concept of idealism in elementary school learning. The research results show that the idealistic conception is reflected in a learning approach that emphasizes the development of moral values, creativity, and understanding abstract concepts. Teachers in elementary schools are expected to be facilitators in encouraging students' critical and reflective thinking and guiding them towards a deeper understanding of life values. Apart from that, this research also highlights the challenges and opportunities in applying the concept of idealism in learning in elementary schools. This challenge involves integrating abstract concepts into a curriculum that sometimes focuses on purely cognitive aspects. However, the opportunities involve the potential to create learning environments that support students' spiritual and moral development. This research contributes to further understanding of the implementation of the philosophical conception of idealism in the context of basic education, with the hope of providing useful guidance for the development of more holistic and value-oriented learning strategies..